Tonsillectomy for Obstructive Sleep‐Disordered Breathing: Should They Stay, or Could They Go?. (21st October 2021) - Friedman, Norman R.; Meier, Maxene; Tholen, Kaitlyn; Crowder, Renee; Hoefner‐Notz, Regina; Nguyen, Thanh; Derieg, Sarah; Campbell, Kristen; McLeod, Lisa
Abstract : Objectives/Hypothesis: Children who do not require oxygen beyond 3 hours after surgery and pass a sleep room air challenge (SRAC) are safe for discharge regardless of polysomnogram (PSG) results or comorbidities. Study Design: Cross‐sectional prospective study. Methods: All children observed overnight undergoing an adenotonsillectomy for obstructive sleep‐disordered breathing were prospectively recruited. Demographic, clinical, and PSG characteristics were stratified by whether the patient had required oxygen beyond 3 hours postoperatively (prolonged oxygen requirement [POR]) and compared using t test, chi‐squared test, or Fisher's exact test depending on distribution. Optimal cut points for predicting POR postsurgery were calculated using receiver operating characteristic curves. The primary analysis was performed on the full cohort via logistic regression using POR as the outcome. Significant characteristics were analyzed in a logistic regression model, with significance set at P < .05. Results: A total of 484 participants met the inclusion criteria. The mean age was 5.65 (standard deviation = 4.02) years. Overall, 365 (75%) did not have a POR or any other adverse respiratory event. In multivariable logistic regression, risk factors for POR were an asthma diagnosis ( P < .001) and an awake SpO2 <96% ( P = .005). The probability of a POR for those without asthma and a SpO2 ≥ 96% was 18% (95% confidence interval: 14–22). Age, obesity, and obstructive apnea/hypopnea index were not associated with POR. Conclusions: In conclusion, all children in our study who are off oxygen within 3 hours of surgery and passed a SRAC were safe for discharge from a respiratory standpoint regardless of age, obesity status, asthma diagnosis, and obstructive apnea/hypopnea index. Additional investigations are necessary to confirm our findings. Level of Evidence: 3 Laryngoscope, 132:1675–1681, 2022